Adaptation of Postural Reactions in Seated Positions and Influence of Head Posture when Exposed to a Single Sideway Perturbation: Relevance for Driving on Irregular Terrain - Tobias C Stenlund; Fredrik Ohberg; Ronnie Lundstrom; Ola Lindroos; Charlotte K Hager; Gregory Neely; Borje Rehn (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2016)
Background and objectives: Mechanical perturbations in seated positions caused by driving on irregular terrain destabilize the driver which, combined with the drivers' posture, may cause musculoskeletal disorders. The aim of this study was to investigate adaptation and the effect of different head postures on seated postural reactions caused by perturbations.  Materials and Methods: Twenty healthy male participants, aged 18-43 years, were tested on a movable platform delivering 15 sideways perturbations (peak acceleration 13.3 m/s2) while the participants held their head in a neutral or a laterally flexed posture. Surface electromyography (EMG) signals were recorded bilaterally in upper neck, trapezius, erector spinae and external oblique, while kinematics were recorded with inertial sensors for the head, trunk and pelvis. EMG amplitudes, muscle onset latencies and angular displacements in the frontal plane were analyzed.  Results: In the neutral position, the EMG amplitudes and neck angular displacements significantly decreased by 0.2% and more than 1.6° respectively after repeated perturbations. Muscle onset latencies remained unchanged. During lateral flexion of the head, the EMG amplitudes decreased by 0.5% but the muscular onset latencies increased by more than 9 ms.  Conclusion: The developed neuromuscular strategy seem to prefer a reduced EMG amplitude. The modest size of the postural reactions during the conditions presented here do not by themselves explain the musculoskeletal disorders found in drivers.